HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP DENGAN PERILAKU MASYARAKAT DALAM PEMILAHAN SAMPAH RUMAH TANGGA DI DESA GUNAKSA KLUNGKUNG TAHUN 2022 - Kadek Cristina; Mochammad Choirul Hadi; I Made Bulda Mahayana; Iin Indayani (Jurnal Kesehatan Lingkungan (JKL), 2023)
Abstract : Gunaksa Village is one of the villages in Dawan Sub-district where some people donot sort the waste they collect, so that at TOSS Werdhi Guna, the officers sort it again. Purpose of research this that is for know level knowledge and attitude with behavior public in sorting rubbish House stairs in the village Use . Type This research is a cross sectional study. This study used  58  samples.  Data  collection  was carried  out  using  a  one-way questionnaire and sheet observation . Results from study this is known that level knowledge with behavior public in sorting rubbish showed by p-value0.000 where results this 0.05 = 0.523 and attitudes with people's behavior in sorting rubbish House ladder showed by p-value 0.000 where results This0.05 = 0.587 which is the level of the moderate relationship. So it can be concluded that there is a relationship between knowledge and attitudes with people's behavior in sorting rubbish households in Gunaksa Village. It is hoped  that the  Puskesmas  in  the  working  area  of  Gunaksa  Village  and community  leaders  will provide  counseling  about  what  impacts  will  be caused by not carrying out waste sorting.